The distribution of college graduate debt, 1990 to 2008: A decomposition approach - Brad J. Hershbein; Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2014)
Despite tremendous recent interest in the subject of student debt by both researchers and policy makers, little is known about how the distribution of college graduate debt has been evolving and what factors can explain it. We use National Postsecondary Student Aid Study data from 1990 through 2008 to document the evolution of college graduate debt profiles. We find that growth in debt over the 1990s was rapid and occurred throughout the distribution; during the 2000s, in contrast, debt grew appreciably only for the top quartile. Employing several decomposition techniques, we exploit the richness of the data to explain these shifts. Over the entire horizon, observable characteristics of students and institutions explain about one-third of the debt increase, though this share tends to be higher around the extensive margin and the median and lower in the right tail. While observables-largely costs-explain a majority of the increase between 1990 and 1996 and again from 2000 to 2008, they explain nothing over the late 1990s. We offer suggestive evidence that this 'unobservable' share was supply-side driven, owing to the advent of both federal unsubsidized Stafford loans and private loans.
Keywords: I22; J24; 330; student loans; higher education; NPSAS; Oaxaca-Blinder decomposition; semiparametric reweighting; recentered influence functions